Translating political discourse: a critical review of studies in Western and Chinese contexts - Sun, Aina; Subramaniam, Vijayaletchumy A/P (Academy Publication, 2023)
The translation of political discourse serves as a linchpin in promoting intercultural dialogue, strengthening diplomatic relations, and advancing international cooperation. This study offers a critical analysis of the translation of political discourse within Western and Chinese paradigms. It commences with a brief introduction to the subject under investigation, succeeded by a discussion on the intercultural salience of political discourse. Subsequently, the paper engages in a comprehensive review of seminal research in the field, elucidating pivotal findings and adopted methodologies. Building upon this analytical framework, the paper delineates prominent lacunae in existing knowledge. This endeavor seeks to galvanize focused research efforts, invigorating the domain of political discourse translation studies and encouraging a global exploration of untapped territories and cross-cultural communication strategies.